Needs assessment for adapting TB directly observed treatment intervention programme in Limpopo Province, South Africa: A community-based participatory research approach - Jabu T. Mabunda; Lunic B. Khoza; Hubertus B. Van den Borne; Rachel T. Lebese (AOSIS, 2016)
Background: Limpopo Province is one of the hardest hit by tuberculosis and human immune virus infections in the country. The province has been implementing directly observed treatment strategy since 1996. However, the cure rate was 64% in 2015 and remains far from the set target by the World Health Organization of 85%. Poor health-care seeking and adherence behaviours were identified as major risk behaviours. Aim: To apply a community-based participatory research approach in identifying barriers and facilitators to health-care seeking and adherence to treatment, and to determine strategies and messages in order to inform the design of an adapted intervention programme. Setting: This study was conducted in three districts in the Limpopo Province, Capricorn, Mopani and Sekhukhune districts. Methods: Community participatory research approach was applied. Purposive sampling was used to sample participants. Focus group discussions were used to collect data. Participatory analysis was used comparing findings within and across all the participants. Results: A total of 161 participated in the study. Participants included coordinators, professional nurses, supporters and patients. Major modifiable behavioural-related barriers were lack of knowledge about tuberculosis, misinformation and misperceptions cultural beliefs, stigma and refusal of treatment support. Environment-related barriers were attitudes of health workers, lack of support by family and community, lack of food and use of alcohol and drugs. Strategies and messages included persuasive and motivational messages to promote healthy behaviour. Conclusion: Joint programmatic collaboration between the community and academic researchers is really needed for interventions to address the needs of the community. Keywords: Health seeking, Adherence, Community based participatory research, Tuberculosis